2001
DOI: 10.1111/j.1600-0447.2001.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in adolescents and young adults with suicidal behaviour

Abstract: Objective: Gender differences in prevalence rates of suicide attempts and suicidal thoughts as well as in risk factors for suicide attempts such as traumatic events and mental disorders were investigated in a random sample of 3021 adolescents aged 14–24 years. Method: The M‐CIDI (Composite International Diagnostic Interview) was used to survey suicidal behaviour, DSM‐IV lifetime diagnoses and traumatic events. Results: The female suicide attempters showed suicidal thoughts and suicide attempts significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 18 publications
4
36
0
1
Order By: Relevance
“…Our study reflects previous observations that females display higher rates of suicidal tendencies including suicide attempts. Although prior studies have also demonstrated a greater risk of suicidal behaviour amongst females, it is important to note that other studies have demonstrated that males are more likely to have completed suicide . Bullying and exposure to violence were significantly associated with both depression and suicidal behaviour.…”
Section: Discussionmentioning
confidence: 77%
“…Our study reflects previous observations that females display higher rates of suicidal tendencies including suicide attempts. Although prior studies have also demonstrated a greater risk of suicidal behaviour amongst females, it is important to note that other studies have demonstrated that males are more likely to have completed suicide . Bullying and exposure to violence were significantly associated with both depression and suicidal behaviour.…”
Section: Discussionmentioning
confidence: 77%
“…Adolescent females have greater emotional intensity and more strong emotional reactions to social stimuli, as compared to males, and they also have higher levels of depression (Charbonneau et al 2009;Hyde et al 2008). Additionally, adolescent females are more likely to report suicidal thoughts and attempts than are adolescent males (Kaess et al 2011;Wunderlich et al 2001). According to Kaess et al (2011), one explanation for this gender difference is that adolescent females reported higher levels of internalizing problems and adolescent males reported higher levels of externalizing problems.…”
Section: Gender Victimization and Suicidementioning
confidence: 99%
“…More than a half of all suicides are committed by persons younger than 45 years of age (1). Gender differences have been documented in the rates of suicide attempts and completions (2–4), levels of suicidal intent and lethality (5, 6), choice of method of suicide (7), and suicidal ideation (3, 8).…”
Section: Introductionmentioning
confidence: 99%